Mitos masyarakat terhadap ritual di Candi Songgoriti sebagai warisan pengetahuan budaya lokal - Sulistyorini, Dwi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to reveal the community's treatment of the Songgoriti temple and the grave of its founder, the rituals carried out at the Songgoriti temple and the grave of Mbah Patok along with the offerings and their meaning. This type of research is field research, a descriptive method with a qualitative approach. The research data consists of the behavior of people with beliefs and rituals at the Songgoriti temple and Mbah Patok's grave. Data sources were obtained from informants, events, and documents. Data collection techniques using observation, interviews, and document study. The collected data was analyzed using mythological theory. Every Legi Friday night at Soggoriti Temple and Mbah Patok's grave, 'sajen' and 'cok bakal' are offered and cleaned as a form of respect. The rituals carried out by the people in these two places include the ritual of asking for blessings, the ritual on the 1st of Sura, the village cleansing ritual, and the ritual of self-purification. Projection of the use of rituals for the younger generation as knowledge of local wisdom inherited from ancestors, as social learning and transmission of social heritage from one generation to the next, and inheritance of morals and ethics.